Intercropping efficiency of chickpea (Cicer arietinum) based intercropping system under rainfed condition of Bihar - Alam, M.I. (Annals of Agricultural Research, 2016)
An experiment on Intercropping efficiency of chickpea (Cicer arietinum) based intercropping systemunder rainfed condition was carried out during rabi-seasons of 2009-10 and 2010-11 at Dholi farmof Rajendra Agricultural University, Pusa, (Samastipur), Bihar. Among the row ratio inintercropping systems, chickpea + linseed (6:1) expressed equal yield attributes and grain yield,and harvest index of chickpea than the chickpea + mustard in 6:1 and 6:2 ratio during both theyears. The yield attributes, grain and straw yields, and harvest index of chickpea did not varysignificantly due to fertilizer levels. The yield attributing characters of mustard and linseed werehigher at 6:1 row ratio of intercropping than sole crops. The 6:2 row ratio of chickpea + mustardand chickpea + linseed recorded maximum grain and straw yields of mustard and linseed whichwere significantly higher over their 6:1 row ratio in both the years. Application of 100% and 75%RDF recorded similar grain yields of mustard and linseed and both turned significantly superiorover 50% RDF in both the years. Chickpea + mustard irrespective of their row ratios recordedsignificant reduction in number of Helicoverpa larvae/10 plants, number of damaged pods/plantand pod damage percentage over chickpea + linseed and sole chickpea. Higher value of numberof Helicoverpa larvae/10 plants, number of damaged pods/plant and pod damage percentage wererecorded at 100% RDF than the lower levels of fertilizer but fails to exert significant effect onthese indices except to pod damage percentage which were significantly more at 100% RDF than50% RDF. Land equivalent ratio (LER) did not vary significantly among the row ratio inintercropping systems, only 6:1 row ratio of chickpea + mustard recorded significantly higherLER (1.15 and 1.16) over sole chickpea in both years. LER did not vary significantly among differentfertilizer levels. Chickpea + mustard in 6:1 row ratio altogether recorded maximum chickpeaequivalent yield (CEY) (2233 and 2501 kg ha-1) and net return (Rs. 44828 ha-1) however, B: C ratio(BCR) was higher under 6:2 row ratio of chickpea + mustard (2.10) which was at par with 6:1 rowratio of chickpea + mustard (2.08). Chickpea + mustard in both the row ratio recorded significantlyhigher CEY, net return and B:C ratio over chickpea + linseed in both the row ratio and solechickpea. CEY, gross and net returns, BCR and LER did not varied significantly among the fertilizerlevels.